Variation in the Indian summer monsoon intensity during the Bolling-Allerod and Holocene - Kessarkar, P.M.; Rao, V.P.; Naqvi, S.W.A.; Karapurkar, S.G. (American Geophysical Union, 2013)
Variations in the Indian summer monsoon (ISM) intensity during the last 16.7 ka have been studied using organic carbon (C org ), delta 15 N of sedimentary organic matter, CaCO 3 , sediment texture, delta 18 O C , and Mg/Ca-derived sea surface temperature, delta 18 O of sea water and sea surface salinity, in a 14 C-dated sediment core from the eastern Arabian Sea. The delta 18 O in water and planktonic foraminifera shells off the central west coast of India may be controlled by the ISM intensity as this area receives high precipitation and land runoff. Also, the C org and CaCO 3 contents of sediments and delta 15 N of sedimentary organic matter may be linked to ISM-induced productivity and denitrification. The results of the present study reveal that between 16 and 15.2ka BP, the ISM was weak with minor fluctuations and started intensifying around 15.2ka BP, at the onset of the Bolling-Allerod (B-A) event. The B-A event is characterized by higher water column denitrification rates comparable to the present day. The ISM signatures observed in the delta 18 O C record of B-A event compare well with those from Timta cave of the western Himalayas and also the Asian summer monsoon signatures from the Hulu caves in China and warming signatures in Greenland Ice Sheet Project 2 (GISP2) suggesting atmospheric teleconnections through Intertropical Convergence Zone. The boundary between the Younger Dryas and the Holocene is discernible with small episodes of abrupt events of increased ISM intensity. This decrease in delta 18 O C values at~11.8ka BP is contemporary with June solar insolation maximum at 30° north and the increase in methane in the GISP2 ice core supporting episodes of warmer climate and increase in ISM intensity. The ISM seems to have been most stable between 7 and 5.6ka BP. The core exhibits periodicity of 500 years that is comparable to the Atlantic water formation and the Chinese monsoon